2004
DOI: 10.1021/ja0446449
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Nanotubes as Functional Architectures with Embedded Fluorescence and Recognition Capabilities

Abstract: A limited combinatorial strategy was used to synthesize a small library of soft lipid-based materials ranging from structurally unordered fibers to highly uniform nanotubes. The latter nanotubes are comprised of a bilayer structure with interdigitated alkyl chains associated through hydrophobic interactions. These tubes contain accessible 2,6-diaminopyridine linkers that can interact with thymidine and related nucleosides through multipoint hydrogen bonding, thereby quenching the intrinsic fluorescence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Potential medical and biological applications using self-assembled LNTs and polymer nanotubes are gradually in progress, including controlled drug release, 82 gene delivery, 83 cell adhesion, 84 antimicrobial activity, 85 helical crystallization of proteins, 86 and biomolecule sensing. 87 The alignment and ordered arrays of the solid LNTs on a substrate [88][89][90] are also important issues for their practical use. At the same time, unveiling the mechanical properties of a single piece of LNT by us and other research groups is also developing and gaining a lot of interest.…”
Section: Future Aspectsmentioning
confidence: 99%
“…Potential medical and biological applications using self-assembled LNTs and polymer nanotubes are gradually in progress, including controlled drug release, 82 gene delivery, 83 cell adhesion, 84 antimicrobial activity, 85 helical crystallization of proteins, 86 and biomolecule sensing. 87 The alignment and ordered arrays of the solid LNTs on a substrate [88][89][90] are also important issues for their practical use. At the same time, unveiling the mechanical properties of a single piece of LNT by us and other research groups is also developing and gaining a lot of interest.…”
Section: Future Aspectsmentioning
confidence: 99%
“…42,24 Among this class of compounds, sophorolipids, natural bolaform glycolipids, can be obtained from the fermentation process of the yeast Starmerella bombicola (Figure 1a) and are the best bioderived candidates to substitute their synthetic counterparts previously studied, 43,44 both in terms of properties and conditions of productions. 45,46 Even if predictions cannot be done, it has been empirically observed that fibers with nanoscale chirality can be formed in glycolipid-based systems if specific sugar-to-lipid linkers like phenyl, 15 phenylamide 47 or amidopyridine 48 groups are used over simple ether bonding. 15 The former enhance hydrogen bonding 47,49,35 or π−π stacking whereas the latest only promote the formation of micelles.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The tubular structure may also act as a physical shield that protects the loaded materials from potential environmental damage. [7] For example, the fluorescence of a CdS-ND-embedded LNT (hereafter abbreviated as CdS-LNT) should be brighter than that of organic nanotubes [8] and gels [9] self-assembled from fluorescent amphiphiles. Therefore, the fluorescence of the CdS-LNT is easily distinguishable and resistant to photobleaching.…”
mentioning
confidence: 99%